Retrospective Evaluation of Patients Diagnosed With Pulmonary Thromboembolism in the Emergency Department (Annals of Medical Research, 2021)
Aim: Pulmonary thromboembolism (PTE) is a major health problem. The aim of this study was the retrospective evaluation of patients diagnosed with pulmonary thromboembolism in the emergency department with regard to underlying risk factors, diagnostic procedures, treatment modalities, mortality rates and mortality-related factors.
Keywords: s: Pulmonary Thromboembolism, Mortality, Heparin, Prophylaxis